Retention Strategies for Technical Talents in the Technological Sector - Abdulmaleek Olawale ABDULAZEEZ; Uthman Opeyemi ADIGUN; Lateef Damilare OLUSESI (Journal of Human Resource Management)
Purpose – Despite the growing recognition of human capital as a key driver of organizational success, many technological companies in Lagos State face persistent challenges in retaining skilled employees. This study addresses the gap by exploring how well current retention strategies, such as rewards, empowerment initiatives, and employee development programs, mitigate turnover. Aims(s) – This study examines the retention of technical talents in selected technological companies in Lagos State. Specifically, it examines the influence of reward, empowerment, training and employee engagement on the retention of technical talents in selected technological companies in Lagos State. Design/methodology/approach. The study employed a descriptive research design with a population of 215 employees from Hudson Global Limited and Rifnote Media, Lagos State. Proportional sampling techniques were used, and data were analyzed through multiple regression. Findings – Results revealed that there is a significant influence of rewards on employee retention (β = 0.222, t = 7.774, p = 0.000 < α =0.05); there is a significant influence of empowerment on employee retention (β = 0.336, t = 7.684, p = 0.000 < α =0.05); there is a significant influence of training on employee retention (β = 0.222, t = 7.256, p = 0.000 < α =0.05); there is a significant influence of employee engagement on employee retention (β = 0.082, t = 2.214, p = 0.028 < α =0.05). Limitations of the study – A small sample size, which may limit the generalizability of the findings. Additionally, the study's reliance on self-reported data from employees may introduce bias into the findings. Practical implications – rewards, employee empowerment, training and employee engagement play a crucial role in influencing employee retention. Organizations are encouraged to refine these strategies to enhance job satisfaction and reduce turnover rates. Originality/value – The insights provided by this study can inform organizational strategies aimed at enhancing employee retention.